A visualization system for erectile vascular dynamics - Fujimoto, Kota; Hashimoto, Daiki; Kashimada, Kenichi; Kumegawa, Shinji; Ueda, Yuko; Hyuga, Taiju; Hirashima, Tsuyoshi; Inoue, Norimitsu; Suzuki, Kentaro; Hara, Isao; Asamura, Shinichi; Yamada, Gen (Frontiers in Cell and Developmental Biology, 2022)
Erection is an essential process which requires the male penis for copulation. Such copulatory process depends on the vascular-dynamic regulation of the penis. The corpus cavernosum (CC) in the upper (dorsal) part of the penis plays a major role in regulating blood flow inside the penis. When the CC is filled with blood, the sinusoids including micro-vessels, dilate during erection. The CC is an androgen-dependent organ and various genital abnormalities including erectile dysfunction (ED) are widely known. Previous studies have shown that androgen deprivation by castration results in a significantly decreased smooth muscles of CC. Experimental works in erectile biology have previously measured intracavernosal penile pressure and mechanical tension. Such reports analyze limited features without assessing the dynamic aspects of the erectile process. In the current study, we established a novel explant system enabling direct visual imaging of the sinusoidal lumen to evaluate the dynamic movement of the cavernous space. To analyze the alternation of sinusoidal spaces, micro-dissected CC explants were incubated by patent blue dye injection and examined for its structural alternations during relaxation/contraction. Dynamic process of relaxation/contraction was analyzed with various external factors administered to the CC. The system enabled imaging of relaxation/contraction of the lumens of the sinusoids and the collagen containing tissues. Histological analysis on the explant system also showed the relaxation/contraction. Thus, the system mimics the regulatory process of dynamic relaxation/contraction in the erectile response. The current system also enabled evaluating the erectile pathophysiology. In the current study, the lumen of sinusoids relaxed/contracted in castrated mice similarly with normal mice. These results suggested that the dynamic erectile relaxation/contraction process was similarly retained in castrated mice. However, the system also revealed decreased duration time of erection in castrated mice. The current study is expected to promote further understanding of the pathophysiology of ED, which will be useful for new treatments in the future. Hence, the current system provides unique information to investigate the novel regulations of erectile function, which provide tools for analyzing the pathology of ED.